2020
DOI: 10.1016/j.jhydrol.2019.124240
|View full text |Cite
|
Sign up to set email alerts
|

A control volume scheme using compact integrated radial basis function stencils for solving the Richards equation

Abstract: A control volume scheme using compact integrated radial basis function stencils for solving the Richards equation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…Eqs. (2) and 3were free from the mass conservation problem. The water-based Richards' equation as in Eq.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eqs. (2) and 3were free from the mass conservation problem. The water-based Richards' equation as in Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Richards' equation consists of a governing equation that is used to describe water flow in subsurface porous media such as soil [1]. It is continuously subjected to numerical investigation [2][3][4][5][6][7][8][9].The modeling of water distribution using the equation has important application in climate science, agriculture and also ecosystem management [10]. Among many applications, Zeide [11] has reported the use of Richards' equation in the tree growth modeling prediction.…”
Section: Introductionmentioning
confidence: 99%
“…To do so we consider the new developed code MH-Lump-1D/2D in which the ML technique is implemented for both porous matrix and fractures and a modified version, called MH-Cons-1D/2D, in which ML technique is used only for porous matrix elements and the standard consistent form is used for fractures. To compare these models, we consider the challenging case of infiltration in a dry soil with imposed heads at the top and bottom surfaces (Huang et al 1996;Ngo-Cong et al, 2020). Beside the nonlinearity related to RE, this problem involves an extremely moving sharp front that cannot be captured numerically without introducing dense grids and small time step size.…”
Section: Advantages Of the ML Technique For Fracturesmentioning
confidence: 99%
“…In contrast to the imposed flux boundary condition, the Dirichlet boundary conditions imposed at the soil top surface compound the numerical difficulties as they require an appropriate approach for the evaluation of the equivalent hydraulic conductivity (Belfort et al, 2013). This problem has been widely investigated in the literature and the common question is to develop an accurate solution in such a case (Forsyth and Pruess, 1995;Huang et al, 2002;Arico et al, 2012;Younes et al, 2013;List and Radu, 2016;Islam et al, 2017;Zha et al, 2017;Ngo-Cong et al, 2020). All the exiting studies suggested appropriate numerical solutions for non-fractured domains.…”
Section: Advantages Of the ML Technique For Fracturesmentioning
confidence: 99%
See 1 more Smart Citation